Blueberry and mulberry juice prevent obesity development in C57BL/6 mice. - Tao Wu; Qiong Tang; Zichun Gao; Zhuoping Yu; Haizhao Song; Xiaodong Zheng; Wei Chen (PLoS ONE, 2013)
OBJECTIVES:To establish whether blueberry (Vaccinium ashei) and mulberry (Morus australis Poir) juice, anthocyanin rich fruit juice, may help counteract obesity. DESIGN:And Methods: Four-week-old C57BL/6 mice were fed a high-fat diet (HFD) with or without blueberry and mulberry juice for 12 weeks. Body weight, serum and hepatic lipids, liver and adipose tissues morphology, insulin and leptin were assessed. RESULTS:Mice fed HFD exhibited increased body weight, insulin resistance, serum and hepatic lipids. In comparison, blueberry and mulberry juice inhibited body weight gain, decreased the serum cholesterol, reduced the resistance to insulin, attenuated lipid accumulation and decreased the leptin secretin. CONCLUSION:These results indicate that blueberry and mulberry juice may help counteract obesity.